A Prospective Comparative Study on the Incidence and Predictors of Difficult Intubation in Cardiac Versus Non-Cardiac Surgical Patients in a Tertiary Care Centre - Jones Deepan Kumar; Sudarsan Kasthuri; Kaapian Thamizholi; Amar Nandakumar; Jeevithan Shanmugam (National Board of Examinations Journal of Medical Sciences)
Introduction: Airway management is sometimes difficult and it remains a significant reason for anaesthesia-related morbidity and mortality. Cardiac surgical patients, due to comorbidities and anatomical challenges, are thought to be at higher risk of intubation difficulties. However, limited Indian data exist comparing the incidence and prevalence of difficult intubation between cardiac and other surgical patients. The current research aims at assessment and comparison of the incidence and predictors of difficult intubation in these two patient groups. Materials and Methods: A prospective observational study was conducted at a tertiary care centre over a six-month period. Under general anaesthesia 400 patients aged over 40 years undergoing elective or emergency cardiac and non-cardiac surgeries (others) were involved. Results: Among the 400 patients (200 in each group), difficult intubation (IDS >5) was observed in 19.5% of cardiac patients compared to 3% in non-cardiac patients (p<0.001). Cardiac patients had significantly higher BMI, Mallampati scores, and neck circumference, with lower thyromental measurements. Hypertension and BMI were significantly associated with higher IDS in cardiac patients. Most airway assessment parameters statistically significant differences between the two groups (p<0.001). Conclusion: Patients who had undergone cardiac surgeries are at a significantly higher risk for difficult intubation. Preoperative identification of high-risk patients using a combination of bedside airway assessments is essential. The Intubation Difficulty Scale is a useful parameter for quantifying intubation complexity in clinical practice.